ISO 27001 As Information Security Solution In Society 5.0 Era: Systematic Literature Review - Nurbojatmiko, Nurbojatmiko; Karimiyah, Muhammad Sharhan Khatami; Asnadi, Nur Muhammad; Anisyah, Rifka (Sinkron : jurnal dan penelitian teknik informatika, 2025)
In the era of Society 5.0, information security is an important issue along with the increasing use of technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and big data. ISO 27001 acts as a globally recognized standard framework for managing information security. The ISO 27001 standard provides a systematic framework for identifying, assessing, and managing information security risks so as to ensure the integrity, confidentiality, and availability of data in an organization. This research aims to evaluate the implementation of ISO 27001 as an information security solution in the Society 5.0 era through a systematic literature review. Using the Systematic Literature Review (SLR) method, this research collects and analyzes relevant literature to identify benefits, challenges, and recommendations related to the application of ISO 27001 in an era of increasingly integrated technology. The results showed that the implementation of ISO 27001 in the Society 5.0 era proved to make a significant contribution in improving organizational information security. This is done through a PDCA (Plan-Do-Check-Act) approach that integrates information security policies into business processes, strengthens risk management, technology infrastructure, and human resource competencies. In conclusion, the implementation of ISO 27001 in the Society 5.0 era not only improves information security, but also supports the achievement of operational efficiency and organizational sustainability amid rapid technological developments.